Bez nadziei - Adamus, Julia; Barańczak, Maciej; Bartkowiak, Aleksandra; Bełza, Magdalena; Bieliński, Dawid; Biernat, Zofia; Chomiak, Oliwia; Ciszewska, Maja; Drożdżyński, Adam; Gozik, Michał; Janiczek, Zuzanna; Janik, Kacper; et al. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Without Hope" is a collection of short stories focused on the problems and experiences of contemporary youth and young adults. The authors address themes such as love, obsession, violence, loneliness, loss, coming of age, and the consequences of difficult choices. The stories combine psychological, thriller, and social conventions, often portraying extreme emotions and the darker aspects of interpersonal relationships. The publication presents diverse experiences of a generation struggling with uncertainty, fear, and emotional crises in the modern world.
Keywords: opowiadanie polskie - 21 w.; literatura współczesna; młodzież; dojrzewanie; relacje międzyludzkie; przemoc; trauma; miłość; kryzys emocjonalny; thriller psychologiczny; short stories; contemporary literature; youth; coming of age; interpersonal relationships; violence; love; emotional crisis; psychological thriller